Effects of long-term grazing disturbance on the belowground storage of organic carbon in the Patagonian Monte, Argentina - Larreguy, Cecilia (2014)
The objective of this study was to analyze the effect of grazing disturbance on the amount and the spatial distribution (vertical and horizontal) of root biomass and soil organic carbon (SOC) in order to evaluate whether grazing alters the belowground storage of organic carbon (C) in arid rangelands of the Patagonian Monte. We selected three representative sites (3 ha each) with low, moderate and high grazing disturbance located far, mid-distance and near the watering point, respectively, in rangelands submitted to sheep grazing for more than 100 years. We assessed the canopy structure and identi fi ed the four most frequent plant patch types at each site. We selected four replications of each patch type and extracted a soil sample (0 e 30 cm depth) underneath the canopy and in the middle of the nearest inter-patch bare soil area in winter and summer. We assessed the root and soil dry mass and the respective organic C concentration in each sample and then we estimated the total belowground organic C storage at each site. Total plant and perennial grass cover were lower with high than low grazing disturbance while the reverse occurred with dwarf shrub cover. High grazing disturbance led to the increase in total root biomass in the whole soil pro fi le of patch areas and in the upper soil of inter-patch areas. SOC was higher in patch than in inter-patch areas at all sites but at both areas was reduced with high grazing disturbance. This was probably the result of the low total plant cover and the low and recalcitrant contribution of above and below-ground plant litter to soils at sites with high grazing disturbance. Accordingly, these changes did not result in variations in the total belowground organic C storage. We concluded that high grazing disturbance did not affect the total belowground organic C storage but led to changes in the spatial patterning of this organic C storage (i.e shifting from soil to roots).